The utility of quantitative 18F-FDG PET/CT-derived parameters as prognostic factors for predicting overall survival in radioiodine-refractory differentiated thyroid cancer - Mai Son; Nguyen Phuong; Le Ha (Asia Oceania Journal of Nuclear Medicine and Biology, 2025)
Objective(s): This study investigates the relationship between quantitative 18F-FDG PET/CT metabolic parameters and overall survival (OS) in patients with radioiodine-refractory differentiated thyroid cancer (RAI-R DTC). Methods: We conducted a prospective analysis of 127 patients with RAI-R DTC. Quantitative metabolic parameters including SUVmax, SUVmean, SUVpeak, total metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were assessed in 18F-FDG -avid recurrent or metastatic lesions via 18F-FDG PET/CT imaging. Patients were monitored for disease progression and mortality for at least one-year post PET/CT imaging. Receiver operating characteristic (ROC) curves were used to establish cut-off values for predicting 5-year mortality, while the Kaplan-Meier method estimated the 5-year survival rate. Univariate and multivariate Cox regression analyses identified prognostic factors associated with OS. Results: The metabolic parameters derived from 18F-FDG PET/CT demonstrated high sensitivity and specificity for predicting 5-year OS. ROC curve analysis established optimal cut-off values for SUVmax (20.27 g/mL), SUVmean (7.46 g/mL), SUVpeak (7.8 g/mL), TLG (45.74 g/mL×cm³), and MTV (5.78 cm3) (AUC: 0.82, 0.78, 0.82, 0.82, and 0.86, respectively; p<0.001). Kaplan-Meier analysis revealed significantly lower OS in patients with higher values of these parameters compared to those with lower ones (survival rates: 42.1% vs. 95.6%, 65.5% vs. 96%, 52.3% vs. 96.3%, 46.5% vs. 97.3%, and 57.3 % vs. 98.3%, respectively; p<0.001). Univariate Cox regression identified SUVmax, SUVmean, SUVpeak, TLG, and MTV as significant predictors of 5-year OS (p<0.05). In multivariate analysis, SUVpeak and MTV emerged as independent predictors of OS. Conclusion: Quantitative 18F-FDG PET/CT-derived parameters are significant predictors of 5-year OS, exhibiting high sensitivity and specificity. Elevated values of these parameters correlate with increased mortality rates. Our findings suggest that SUVpeak and MTV are independent prognostic factors for 5-year OS in patients with radioiodine-refractory DTC.